Inspector X and the Eternal City. - Chong, Yew Meng. (2008)
The drama is a tongue-in-cheek noir vision of a futuristic city that becomes a larger-than-life tourist playground plagued by greed, gambling and terrorism. It is an allegory about innocence loss.